Linking Perceived Supervisory Support and Self-Efficacy for Change to Individual Readiness for Change - Haqq, Zulkifli Nurul; Nurhayati, Nurhayati; Sharom, Nur Qamarina; Ismail, Farah Laili Muda (Jurnal Bisnis dan Manajemen, 2021)
Dynamic business environment often forces many organizations to make change immediately, especially in the current coronavirus disease 2019 (COVID-19) pandemic outbreak. In turn, organizations need to make sure that their members accept and support change. The purpose of this research is to examine the role of supervisory support by using social exchange theory and self-efficacy for change by using social learning theory in predicting the multidimensional of individual readiness for change (i.e., cognition, affection, and intention). Also, this research sought to examine the mediation role of self-efficacy for change in the relationship between supervisory support and individual readiness for change. A total of 96 employees from Islamic Rural Bank in East Java, Indonesia has participated in this research. Partial least square structural equation modelling (PLS-SEM) is employed for analysing research hypotheses and revealed that the higher perceived supervisory support and self-efficacy for change, the higher cognitive, affective, and intentional readiness for change. Finally, this paper recommends several implications that worth considering, both theoretically and practically.